The learning camera: A personalized learning model for online pedagogy in human services education. Issue 4 (2nd October 2019) - Corbin, Hope J.; Chandran, Devyani; Van Wingerden, Christina; Baker-Sennett, Jacquelyn
Abstract: This article describes the development of a personalized learning approach to human services online education that utilizes a "learning camera" as a metaphorical tool for undergraduate students' development of knowledge, skills, and dispositions required for successful transition to professional practice. By highlighting students' ongoing development as knowledge builders and constructivist learners, the online curriculum is enacted within each student's area of interest and in their home communities. This "learning camera" model of online pedagogy for human services education is intended to serve as a resource for other institutions interested in praxis-oriented approaches to personalized online teaching and learning.